Short-pulse laser-driven x-ray radiography - Brambrink, E; Baton, S; Koenig, M; Yurchak, R; Bidaut, N; Albertazzi, B; Cross, J; Gregori, G; Rigby, A; Falize, E; Pelka, A; Kroll, F; et al. (Cambridge University Press, 2016)
We have developed a new radiography setup with a short-pulse laser-driven x-ray source. Using a radiography axis perpendicular to both long- and short-pulse lasers allowed optimizing the incident angle of the short-pulse laser on the x-ray source target. The setup has been tested with various x-ray source target materials and different laser wavelengths. Signal to noise ratios are presented as well as achieved spatial resolutions. The high quality of our technique is illustrated on a plasma flow radiograph obtained during a laboratory astrophysics experiment on POLARs.